Eddy dynamics in the Southern Ocean: How does the interaction of the Antarctic Circumpolar Current with sea-bed topography influence the surface mixed layer and hence the carbon-climate feedback processes? - Kobo, Nomkwezane S; Herbette, S; Monteiro, Pedro MS; Reason, C (2012)
4th CSIR Biennial Conference: Real problems relevant solutions, CSIR, Pretoria, 9-10 October 2012 The Southern Ocean is an important sink for heat and CO2 and is one of the world’s most productive regions. The unique absence of blocking continents allows the Antarctic Circumpolar Current (ACC) to connect all ocean basins (Atlantic, Pacific and Indian). While the dynamics of the SO are dominated by this large meandering current, smaller scale processes are also important. For example, when flow encounters topography the generation of mesoscale features (such as eddies) can result. These mesoscale features influence water mass formation, meridional heat transport and carbon dioxide uptake. This project investigates the how.